ANALISIS KLASIFIKASI KABUPATEN DI JAWA TENGAH BERDASARKAN POPULASI TERNAK MENGGUNAKAN FUZZY CLUSTER MEANS - Wilandari, Yuciana; Mukid, Moch. Abdul; Megawati, Nurhikmah; Sutarno, Yulia Agnis (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
One of the fundamental problems that always exist in a regions in Indonesia is the problem of poverty. Various poverty reduction efforts initiated by the Central Government and the Regions is now experiencing growth and significant shifts in accordance with the direction and context of poverty reduction targets. To overcome poverty, one of the things done by the Central Java provincial government is to help livestock. Livestock types cultivated in Central Java, is a large livestock, namely cattle (beef / dairy), buffalo and horses, while small livestock consists of goats, sheep and pigs. For that conducted the study to classifyÂ cities in Central Java into groups based on livestock population. The grouping using fuzzy cluster analysis means. From this study showed that of the three kinds of clusters obtained many tried to do the most accurate cluster is 3 clusters with Xie-Beni index 0,3279177, with cluster 1 are 20 city, cluster 2 are 12 City and cluster 3 there are 3 City.Â Keywords: Classification, Fuzzy Cluster Means, Livestock